Ancient India in Historical Outline : 4th Revised Edition - Jha, Dwijendra Narayan, (Brill | Manohar Publishers & Distributors, 2021)
This is the fourth revised version of the book, which was first published in 1977. It surveys the major developments in India's social, economic and cultural history up to the end of the ancient period and explains the rise and fall of empires with reference to their material bases. It pays special attention to elements of change and continuity and gives the lie to the view that Indian society has been stagnant and changeless, a view propagated by Western scholars in the heyday of British imperialism and which continues to be peddled ingeniously in our own times. It analyses the changing forms of exploitation and social tensions and the role of religion and superstition in curbing them. It also stresses the fact that the achievements of ancient India, remarkable though they were, cannot cover up the social and economic disparities which we have inherited from the past. The assassination of Mahatma Gandhi and the demolition of the Baburi Masjid are two ... unforgettable milestones in the unfolding of the backward-looking Hindu revivalist and fascist politics of contemporary India. Since both Harappa and Mohenjodaro are situated now in Pakistan, the Hindu revivalists are busy locating the epicentre of the Harappan culture in the elusive Saraswati valley. Some Indian historians tirelessly speak of their [the Guptas] rule as a golden age. ... The truly golden age of the people does not lie in the past, but in the future, if at all.